Peran Lembaga Pemasyarakatan dalam Memenuhi Hak Narapidana Perempuan Hamil dan Pasca Melahirkan (Studi di Lembaga Pemasyarakatan Perempuan Kelas II A Kerobokan) - Desy Kristiani Rahma Putri; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
The correctional system is a coaching effort carried out in correctional institutions in Indonesia, the guidance is intended for inmates who commit criminal acts and are sentenced to prison. In the coaching process, the inmates are protected and nurtured by correctional officers and their rights are protected as citizens. The purposes of this study are to reveal the rights of pregnant and postnatal female prisoners in the correctional facility as well as the implementation of granting the rights of pregnant and postnatal women inmates to women's prisons class II A Kerobokan. The research method used is empirical legal research with a sociological juridical approach. The technique of collecting legal materials is obtained directly through respondents or sources. Primary and secondary sources of legal materials were analyzed using descriptive analysis techniques. This study concludes that prisons have an important role in protecting and fulfilling the rights of prisoners themselves, especially pregnant and postpartum women, the protection of these rights is intended so that they receive humane treatment in prisons.